Outline of education in Japan 1997 (The Asia/Pacific Cultural Centre for UNESCO, 1996)
This publication is a reproduction by the Asia/Pacific Cultural Centre for UNESCO, Tokyo, of "Development of Education in Japan 1994 - 1996. Report for submission to the 45th session of the international conference on education", published by the Ministry of Education, Science, Sports and Culture.